2010
DOI: 10.5056/jnm.2010.16.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture on Visceral Hyperalgesia, Serotonin and Fos Expression in an Animal Model of Irritable Bowel Syndrome

Abstract: Background/AimsWhile it is well established that acupuncture relieves somatic pain, its therapeutic effect on visceral pain such as irritable bowel syndrome (IBS) is unclear. We evaluated the effect of acupuncture in treating visceral hyperalgesia in an animal model.MethodsSprague-Dawley rats (n = 8 per group) with prior neonatal maternal separation stress were randomly allocated to receive 3-day treatment of either electroacupuncture (EA) or sham acupuncture at acupoint ST-36. Another group of rats without pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 40 publications
3
50
0
1
Order By: Relevance
“…A facilitatory role for serotonin in visceral pain processing, as demonstrated in the present study, is supported by several studies[27,28]. With regard to the bladder Randich et al showed that bladder hypersensitivity following acute inflammation was significantly attenuated by intrathecal administration of the non-specific serotonergic antagonist, methysergide[7].…”
Section: Discussionsupporting
confidence: 87%
“…A facilitatory role for serotonin in visceral pain processing, as demonstrated in the present study, is supported by several studies[27,28]. With regard to the bladder Randich et al showed that bladder hypersensitivity following acute inflammation was significantly attenuated by intrathecal administration of the non-specific serotonergic antagonist, methysergide[7].…”
Section: Discussionsupporting
confidence: 87%
“…For the EA protocol, acupuncture needles made of stainless steel, size 0.5 mm (Complementar Agulhas, Brazil), were inserted bilaterally in the stomach point 36, ST36 (ZuSanLi), which is located in the anterolateral portion of the hind limb, near the anterior tibial tuberosity, in the tibialis anterior muscle and is innervated by the deep fibular nerve (Tjen et al, 2004;Li et al, 2009). The needling was performed at a depth of 5 mm and confirmed by a slight muscle contraction (Wu et al, 2010) or by slight and repeated movement of the paw (Zhou et al, 2005). The NKL electro-stimulator (Model EL608) with eight channels was used.…”
Section: Electroacupuncture Protocolmentioning
confidence: 99%
“…Basically, it exhibits the physiological impacts on neural, humoral, opioid and serotonegic pathways with the effects of normalized motility, inhibited acid output, antinociceptive effect, reduced rectal hypersensitivity and altered 5-HT functions [170][171][172] . Acupuncture looks promising to treat FGIDs including IBS.…”
Section: Complementary and Alternative Medicinesmentioning
confidence: 99%